Origin of low δ26Mg Cenozoic basalts from South China Block and their geodynamic implications. (1st September 2015) - Huang, Jian; Li, Shu-Guang; Xiao, Yilin; Ke, Shan; Li, Wang-Ye; Tian, Ye
Abstract: Origin of low δ 26 Mg basalts is a controversial subject and has been attributed to interaction of isotopically light carbonatitic melts derived from a subducted oceanic slab with the mantle (Yang et al., 2012), or alternatively, to accumulation of isotopically light ilmenite (FeTiO3 ) in their mantle source (Sedaghatpour et al., 2013). To study the origin of low δ 26 Mg basalts and evaluate whether Mg isotope ratios of basalts can be used to trace deeply recycled carbon, high-precision major and trace element and Mg isotopic analyses on the Cenozoic alkaline and tholeiitic basalts from the South China Block (SCB), eastern China have been carried out in this study. The basalts show light Mg isotopic compositions, with δ 26 Mg ranging from −0.60 to −0.35. The relatively low TiO2 contents (<2.7 wt.%) of our basalts, roughly positive correlations between δ 26 Mg and Ti/Ti ∗ and their constant Nb/Ta ratios (16.4–20) irrespective of variable TiO2 contents indicate no significant amounts of isotopically light ilmenite accumulation in their mantle source. Notably, the basalts display negative correlations between δ 26 Mg and the amounts of total alkalis (i.e., Na2 O + K2 O) and incompatible trace elements (e.g., Ti, La, Nd, Nb, Th) and trace element abundance ratios (e.g., Sm/Yb, Nb/Y). Generally, with decrease of δ 26 Mg values, their Hf/Hf ∗ and Ti/Ti ∗ ratios decrease, whereas Ca/Al and Zr/Hf ratios increase. These features are consistent with incongruent partial melting of an isotopically light carbonated mantle, suggesting that large variations in Mg isotope ratios occurred during partial melting of such carbonated mantle under high temperatures. The isotopically light carbonated mantle were probably formed by interaction of the mantle with low δ 26 Mg carbonatitic melts derived from the deeply subducted low δ 26 Mg carbonated eclogite transformed from carbonate-bearing oceanic crust during plate subduction. As only the Pacific slab has an influence on both the North China Block (NCB) and SCB, our results together with the study of Yang et al. (2012) demonstrate that the recycled carbonatitic melts might have originated from the stagnant Pacific slab beneath East Asia in the Cretaceous and Cenozoic and that a widespread carbonated upper mantle exists beneath eastern China, which may serve as the main source for the <110 Ma basalts in this area. Thus, our study demonstrates that Mg isotope ratios of basalts are a powerful tool to trace deeply recycled carbon.